non-OILExport Promotion Strategy From Per/Capita Income Prespective - seyedmohamad erabi; hasan ghasemi (مطالعات مدیریت بهبود و تحول, 2004)
Export   of  non-oil   products   is  one  of  the  mam   topics   that   has  been investigated by academic, political,  and social circles in recent years and all has concensus  on it's promotion. This topic has been studied from different perspective  mainly from structural and SUPPLY  side, This paper looks at non-oil export from DEMAND  side. With this orientation we have used LINDER, s theory as our theoretical base and further  have  investigated  the effect  of change  in  per/capita  income  on the direction of Iran,s non-oil export. The  result   of  this  study  indicate  that  as  Iranian  per/capita   income  has decreased  ,  lran,s  Non-Oil  export direction  has shifted  from countries  with higher   per /capita   incom   (Europe   continent)   to  countries   with   similar per/capita  income category with Iran. (Asia Continent)